Development of a Tiltrotor Propulsion System for Hybrid VTOL Fixed-Wing Drones - Mohd Fadhli Zulkafli,; Lau Wei Le,; Bong Zhan Yong,; Ahmad Hamdan Ariffin,; Syafiqah Nur Azrie Safri,; Mohd Fauzi Yaakub, (International Journal of Integrated Engineering, 2025)
Hybrid Unmanned Aerial Vehicles (UAVs) integrate features from both fixed-wing and multirotor UAVs. The fixed wings efficiently distribute aerodynamic loads while combining aerodynamic properties with the multirotor configuration. A tiltrotor mechanism is necessary to facilitate the transition between hover and forward flight modes. This research focuses on developing a comprehensive tiltrotor propulsion system for a fixed-wing aircraft. Two methodologies were employed: software simulation and experimental testing. A restricted flight test was conducted using a test rig to observe the drone's behaviour at various throttle levels, revealing that each motor produced 2.12 kg of thrust, resulting in a total thrust of 6.12 kg. The drone successfully lifts off at its maximum take-off weight of 3.1 kg. Five potential materials for the components supporting the front and rear motors were tested through simulations, with Polymaker's PolyTerra PLA, a modified polylactic acid material, proving to be the best option. It demonstrated maximum equivalent von Mises stress values of 4.0122 MPa for the front motor supports and 2.8205 MPa for the rear motor supports, along with minimal deformations of less than 0.01 mm. Therefore, the results demonstrate that Polymaker's PolyTerra PLA is an optimal material for the support components of the front and rear rotors, ensuring structural reliability and suitability for hybrid vertical take-off and landing (VTOL) fixed-wing drones, as evidenced by its exceptional performance under simulated and experimental conditions.